Technical Relevance of Polymer/Cement/Carbon Nanotube Composite: Opportunities and Challenges. (1st November 2016) - Afzal, Anam; Kausar, Ayesha; Siddiq, Muhammad
ABSTRACT: The polymer/cement/carbon nanotube composites are known for piezoelectric properties in intelligent structures. Polymers are also used to fulfill deficiencies in carbon nanotube/cement mortars. High-impact polystyrene has replaced sand to enhanced properties like energy consumption, waste disposal, and environmental pollution. Spray-applied fire-resistive material in engineered cementitious composite may overcome drawbacks of conventional brittle composite. Carbon nanotube is used as nanofillers in ordinary Portland cement due to superior mechanical properties. Cementitious polymer/carbon nanotube composite has potential to determine heat-dependent and self-sensing capacity of composites. Smart properties of composites are measured using conductivity measurement. Polymers are also used for making better carbon nanotube dispersion. GRAPHICAL ABSTRACT: